Qualitative and Quantitative Image Analysis of MRCP Imaging in T2 SS-FSE and T2* FIESTA Fat Saturation - Hernastiti Sedya Utami; Lutfatul Fitriana; Fani Susanto; Pradana Nur Oviyanti (Jurnal Multidisiplin Madani, 2022)
The T2 weighted imaging of coronal MRCP can used a sequence derived from spin echo is the SS-FSE sequence and the gradient echo fast imaging is FIESTA. SS-FSE can be done with the fat saturation technique to suppress the fat signal so that it will be hypointense. The use of the breath-hold technique can also be used in both sequences. This study was to compared the differences in coronal MRCP image information between SS-FSE and FIESTA fat saturation to evaluate their ability to depict the image quality of MRCP. 15 patients performed 2D T2 SS-FSE and FIESTA fat saturation coronal MRCP. The images analyzed by qualitative study that was carried out by MRCP questionnaire which was examined by radiologist. Quantitative analysis was conducted by measuring the signal-to-noise ratio (SNR) values. The result is the FIESTA fat saturation sequence shows better image information and more optimized SNR than the SS-FSE on coronal MRCP because it can reveal more clear and informative anatomy such as common bile duct, pancreatic duct, cystic duct and intrahepatic duct. Finally, FIESTA fat saturation can be used as a effective alternative sequence and can improve billiary system of MRCP image quality